Medicines management support to older people: understanding the context of systems failure. Issue 7 (10th July 2014) - Rogers, Stephen; Martin, Graham; Rai, Gurcharan
Abstract : Objectives: Changing demographics and pressures on the healthcare system mean that more older people with complex medical problems need to be supported in primary and community care settings. The challenge of managing medicines effectively in frail elderly patients is considerable. Our research investigates what can go wrong and why, and seeks insight into the context that might set the scene for system failure. Setting: North London; a district general hospital and surrounding health authorities. Participants: 7 patients who had been admitted to hospital and 16 informants involved in their care. Design: Patients with preventable medication-related admissions were identified in an occurrence screening study. An accident investigation approach was used to create case studies from accounts of staff involved in each patient's care prior to their admission. Structured analysis of case studies according to the accident investigation approach was complemented by a separate analysis of interviews using open coding with constant comparison to identify and illustrate higher-level contextual themes. Outcomes: The study sheds light on care management problems, their causes and the context in which care management problems and their causes have occurred. Results: Care management problems were rooted in issues with decision-making, information support and communications among staff members and between staff, patients and carers. Poor judgement, slips and deviations from best practice were attributed to task overload and complexity. Within general practice, at the interface with community services and with hospitals, we identified disruption to traditional intraprofessional and interprofessional roles, assumptions, channels and media of communication which together created conditions that might compromise patient safety. Conclusions: New ways of working driven by the ethos of productivity are disrupting traditional intraprofessional and interprofessional roles, assumptions, channels and media of communication. Concomitant improvements in communications technology, process and protocol are urgently required to offset potentially serious risks to patient safety.